Buku Ajar Pembelajaran Membaca Bermuatan Teks Cerita Rakyat Melayu Riau - Ayu Rusmani; Asnawi Asnawi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The textbook for learning to read used by students of the Indonesian Language and Literature Education Study Program at the Islamic University of Riau does not contain the text of Riau Malay folklore. Therefore, this study aims to identify the need for reading learning textbooks that contain the texts of Riau Malay folklore. This research is a qualitative research that uses questionnaires and interviews as instruments. Respondents in this study were students in semester 7 class of 2019 in the Indonesian Language and Literature Education study program, Riau Islamic University who took the Reading Learning course. The results of this study provide a description of the needs of reading learning textbooks that contain the text of Riau Malay folklore in accordance with the eligibility standards of textbooks, including aspects of the eligibility of content, presentation, language, and content of Riau folklore.